AgI modified covalent organic frameworks for effective bacterial disinfection and organic pollutant degradation under visible light irradiation - Fuyang Liu; Chenyi Nie; Qiqi Dong; Zhiyao Ma; Liu, Wen; Meiping Tong (Journal of Hazardous Materials, 2020)
Covalent organic frameworks (COFs) have recently been demonstrated to have great application potentials in water treatment. Their photocatalytic performance towards bacterial disinfection and organic pollutant degradation yet has seldom been investigated. In this study, AgI modified COFs (using 2,5-diaminopyridine and 1,3,5-triformylphloroglucinol as precursors) (COF-PD/AgI) were fabricated and their applications to photocatalytically disinfect bacteria and degrade organic pollutants were investigated. COF-PD/AgI exhibited effective photocatalytic performance towards Escherichia coli disinfection and organic pollutant (Rhodamine B and acetaminophen) degradation. SEM images were employed to investigate cell disinfection process, while theoretical density functional theory (DFT) calculation and intermediates determination were used to elucidate organic pollutant degradation processes. Scavenger experiments, ESR spectra and chemical probes experiments confirmed O2−, h+ and OH played important roles in the photocatalytic process. The formation of dual-band Z-scheme heterojunction improved photocatalytic performance. COF-PD/AgI remained high photocatalytic activity in the four consecutive cycles and could serve as a promising photocatalyst for water purification.
Keywords: COF-PD/AgI; Disinfection; Organic pollutant degradation; Reactive species; Z-scheme